EFEITO PÓS-EXERCÍCIO RESISTIDO SOBRE A PRESSÃO ARTERIAL DE MULHERES ADULTAS HIPERTENSAS (Fiep Bulletin - online, 2024)
POST-RESISTANT EXERCISE EFFECT ON BLOOD PRESSURE IN HYPERTENSIVE ADULT WOMEN ABSTRAT The study aimed to verify the acute effect of resistance exercise on blood pressure (BP) in hypertensive adult women. Method: Five women aged between 40 and 50 years old, experienced in resistance training (RT), underwent the 1 repetition maximum (1RM) test in four exercises. After 48 hours of carrying out the 1RM tests, RT sessions were carried out on two non-consecutive days: on the 1st day the two women and on the 2nd day the three women performed the four proposed exercises in three sets of 20 repetitions with a load between 40 and 60% for 1RM, 40 seconds interval between sets and 1 minute between exercises. BP was measured by the researcher after 5 minutes of rest pre-RT and 20 minutes post-RT. Results: A significant change in BP was found after using the protocol. Thus, there was a significant decrease in both systolic and diastolic BP after 20 minutes of performing the RT. Conclusion: The present study demonstrated that RT with a load between 40 and 60% of the maximum causes a significant drop in both systolic and diastolic BP when measured 20 minutes after the end of the exercise session. The research will be an important contribution, as there are still few scientific studies that relate the real benefits of resistance exercise on BP in hypertensive adults.Keywords: Resistance training. Blood pressure. Acute effect.